STRATEGI KREATIF PEMASARAN ZAAFER INDONESIA PADA MEDIA SOSIAL TIKTOK - Hamdan, Al Hafizh Mubarak; Kurniawati, Dewi (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
Marketing communication in today's digital era is growing. With the existence of social media, it further accelerates the promotion path for a company. The emergence of the Tiktok application as a new media is one of the right choices to be used as promotional media, supported by the number of Tiktok users in Indonesia reaching 113 million until April 2023. Zaafer Indonesia uses the Tiktok application as a promotional medium, being unique when using soft selling methods in sales. The purpose of this study is to find out the content of @zaaferindonesia account content in carrying out marketing communication strategies through the Tiktok application. The research method used is qualitative with content analysis techniques used to analyze and understand symbolic messages in forms such as documents, articles, literary works, and others that include unstructured data. This research will be observed using content analysis, product placement and AISAS Model (Attention, Interest, Search, Action, Share) with qualitative descriptive methods. Visual observations on TikTok accounts @zaaferindonesia categorized based on the characteristics of the scene in which there is implicit marketing, lifestyle marketing, and emotional marketing in shaping the brand image of Zaafer Indonesia. This analysis aims to find out how Zaafer Indonesia's creative marketing strategy is in conveying the visual messages contained in the @zaaferindonesia tiktok account. Based on the results of content analysis, product placement and AISAS, it can be concluded that: 1) Zaafer Indonesia Indonesia uses the Tiktok Platform to gain awareness from young people; 2) Even though the product placement displayed is not formally stated, engagement on the @zaaferindonesia tiktok account is quite high; 3) The creative advertising strategy in the @zaaferindonesia tiktok account is conveyed using visual language; 4) Advertisements in the @zaaferindonesia tiktok account use an emotional approach, namely by offering grandeur, masculinity, elegance & beauty. Keywords: Communication, Marketing, Analysis, Content, Tiktok.